Proceedings 20th IEEE International Parallel &Amp; Distributed Processing Symposium 2006
DOI: 10.1109/ipdps.2006.1639556
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the performance of HLA-based simulation systems via software diversity and active replication

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2007
2007

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…This is the case of struct MsgS* and char* parameters, which represent pointers to memory areas that contain data to be accessed by both B-RTI and the federate. For instance, when the ReflectAttributeValues() callback is issued, the struct MsgS* parameter b An early implementation [22] relying on a socket based approach to support the interaction between the replication management modules, has shown that the kernel mode overhead can be affordable only for coarse grain applications.…”
Section: Implementation Detailsmentioning
confidence: 99%
“…This is the case of struct MsgS* and char* parameters, which represent pointers to memory areas that contain data to be accessed by both B-RTI and the federate. For instance, when the ReflectAttributeValues() callback is issued, the struct MsgS* parameter b An early implementation [22] relying on a socket based approach to support the interaction between the replication management modules, has shown that the kernel mode overhead can be affordable only for coarse grain applications.…”
Section: Implementation Detailsmentioning
confidence: 99%
“…Another federate replication structure has been proposed by Quaglia [93,94,95] In this thesis, we shall classify the federate replication structure proposed in [93,94,95] as No-Barrier federate replication structure. In such a structure, replicas of a federate connects to the same DRC through a replication module (e.g., ARML) and they are required to be Piecewise Equivalent.…”
Section: Replicating Federate Executionsmentioning
confidence: 99%